ANALISIS KELAYAKAN FINANSIAL USAHA PERKEBUNAN KARET PROGRAM EKS UPP TCSDP DI DESA KOTO DAMAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Zohrah, Prita Andika; Yusmini, Yusmini; Edwina, Susy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to analyze financial feability of rubber plantation in Koto Damai Village, Kampar Kiri Tengah District. The invesment criterias of this research used Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and sensitivity analysis. Based on data obtained eks UPP TCSDP farmers in Koto Damai Village had 177 Ha of area rubber plantation where a farmer had one hectare. Data were collected from 20 smallholder farmers using simple random sampling. The result of analysis showed that NPV was Rp.81.724.375,24, Net B/C was 3,23, IRR was 26% and obtain the benefit was Rp.4.086.219,24 in a year. Sensitivity analysis can be concluded that rubber production decrease 4% changed NPV Rp.76.003.400,00, while output value decrease 44% changed NPV Rp.18.793.650,00, when input incerease 10% changed NPV Rp.75.594.375,21. The smallholder rubber plantation is still feasible by three variabels because NPV (positive), IRR>SOCC, Net B/C>1.Â Keyword: Rubber, Criterion of Investment, Analyze of sensitivityÂ